Complement C1q and von Willebrand factor interaction in atherosclerosis of human carotid artery - Kristina Schulz; Kristina Schulz; Claudia Donat; Mukesh Punjabi; Katharina Glatz; Beat Kaufmann; Marten Trendelenburg; Marten Trendelenburg (Frontiers in Immunology, 2023)
Atherosclerosis is an inflammatory disease of the vessel wall, with cholesterol crystal (CC) deposition being a hallmark of the disease. As evidence for a cross-talk between complement activation and hemostasis on CC surfaces has been limited to in vitro data, the aim of this study was to demonstrate the presence of C1q-vWF complexes in human atherosclerosis ex vivo. We used immunofluorescence staining and a proximity ligation assay (PLA, Duolink®) to examine the presence, localization, and co-localization of C1q and vWF in frozen sections of human carotid arteries with atherosclerosis or without atherosclerotic changes as well as material from thrombendarteriectomy. We observed significantly higher levels of C1q and vWF in healthy tissue compared to diseased material and greater co-localization in the PLA in healthy samples than in diseased samples. In diseased samples, fluorescence signals were highest in locations encompassing atheroma and foam cells. While there was overall reduced signal in areas with CCs, the staining was spotty, and there was evidence of co-localization on individual CCs. Thus, we demonstrate the presence of C1q-vWF complexes in human carotid arteries ex vivo, which was most abundant in healthy endothelial and subendothelial space and reduced in diseased tissue. C1q-vWF interaction can also be demonstrated on the CC surface.